2015
DOI: 10.1016/j.clml.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

New Therapeutic Approaches in Polycythemia Vera

Abstract: Polycytemia vera (PV) is one of the three Philadelphia-negative myeloproliferative neoplasms. Clinically, PV is an indolent disease but its course can be complicated by arterial and venous vascular accidents, evolution to myelofibrosis or leukemic transformation. Treatment of PV is, therefore, aimed at preventing such acute complications. The cornerstone of therapy of low-risk patients remains strict control of cardiovascular risk factors, the use of phlebotomy and low dose aspirin. Higher risk patients should… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 75 publications
1
10
0
1
Order By: Relevance
“…Interferons have been used in treatment of MPNs, including PV, for almost 40 years, but the high prevalence of side effects have limited their clinical application 15. The novel pegylated form of interferon has advantages of longer half-life, better stability, less immunogenicity and improved tolerance 16.…”
Section: Discussionmentioning
confidence: 99%
“…Interferons have been used in treatment of MPNs, including PV, for almost 40 years, but the high prevalence of side effects have limited their clinical application 15. The novel pegylated form of interferon has advantages of longer half-life, better stability, less immunogenicity and improved tolerance 16.…”
Section: Discussionmentioning
confidence: 99%
“…While the discovery of the Philadelphia chromosome as genetic alteration in CML and the arrival of BCR-ABL targeting TKIs in the clinic have largely replaced the need for IFNα-based treatment in this disease, some recent clinical studies have shown that combination of imatinib and IFNα is superior to either therapy alone, perhaps due to the fact that IFNα targets preferentially CML stem cells (Talpaz et al, 2013 ). Notably, due to its success in numerous clinical trials, IFNα is used as first-line treatment choice for patients with high-risk PV (Barbui et al, 2011 ; Falchi et al, 2015 ). Regardless of the specific use, IFN-based therapies have their limitations due to dose-limiting side effects.…”
Section: Prevention and Therapeutic Interventionmentioning
confidence: 99%
“…La PV puede permanecer clínicamente silenciosa, el 40% de los pacientes relatan síntomas debilitantes. Las manifestaciones clínicas de la enfermedad incluyen síntomas constitucionales (fatiga, prurito y sudores nocturnos), síntomas microvasculares (cefalea, aturdimiento, parestesias acrales, eritromelalgia -síndrome clínico caracterizado por con aumento de la temperatura de la piel y dolor de carácter urente localizado en las extremidades-así como dolor torácico atípico), y complicaciones macrovasculares (trombosis venosa profunda, tromboembolismo pulmonar, accidentes cerebrovasculares, angina inestable e infarto agudo de miocardio) [22]. Aproximadamente el 70% de los pacientes refieren la presencia de prurito acuagénico, que es aquel que es provocado por el contacto con agua.…”
Section: Presentación Clínica Y Diagnósticounclassified